Necrobiosis Lipoidica Diabeticorum. (22nd April 2012) - Scaramuzza, Andrea; Macedoni, Maddalena; Tadini, Gian Luca; De Angelis, Laura; Redaelli, Francesca; Gazzarri, Alessandra; Comaschi, Valentina; Giani, Elisa; Zuccotti, Gian Vincenzo
Abstract : Necrobiosis lipoidica is a rare disorder that usually appears in the lower extremities and it is often related to diabetes mellitus. There are few reported cases of necrobiosis lipoidica in children. We present an interesting case in that the patient developed lesions on the abdomen, which is an unusual location.